Plasma Catecholamines in Long-Term Diabetics with and without Neuropathy and in Hypophysectomized Subjects - Christensen, Niels Juel (1972)
Employing a precise and sensitive double-isotope derivative technique, plasma catecholamine concentration (PCA) was measured in four groups of subjects: (a) long-term diabetics with neuropathy, (b) long-term diabetics without neuropathy, (c) hypophysectomized long-term diabetics with neuropathy, and (d) nondiabetic control subjects. Blood samples were obtained from subjects in the supine and in the standing position. In nondiabetic control subjects, PCA (mainly noradrenaline) increased from 0.26 ng/ml in the supine positon to 0.69 and 0.72 ng/ml 5 and 10 min after assuming the standing position. By plotting this increase in PCA on the y axis in a coordinate system vs. increase in pulse rate, PCA was divided into two components: one of these depended on the rise in pulse rate on standing (called CAH) and the other corresponded to the intercept on the y axis where rise in pulse rate equals zero (CAP). Long-term diabetics with neuropathy showed a significant reduction in PCA in both the supine and the standing position. Further analysis demonstrated that CAP was considerably reduced whereas CAH was normal. Long-term diabetics without neuropahty showed normal PCA values. Surprisingly, hypophysectomized diabetics with neuropathy exhibited mean PCA values in both the supine and the standing position which were similar to those found in the nondiabetic subjects and considerably elevated compared with the findings in the nonoperated, long-term diabetics with neuropathy. Further analysis in terms of CAP and CAH demonstrated, however, that CAP was just as abnormally reduced in the hypophysectomized as it was in the nonoperated patients whereas CAH was considerably increased. In contrast to the findings in the nonoperated diabetics with neuropathy, the hypophysectomized diabetic patients with neuropathy demonstrated a negative correlation between rise in PCA and blood pressure on standing indicating that the increase in PCA was at least partially a compensatory phenomenon in the interest of the maintenance of a normal level of blood pressure. An increased sympathetic tone (vasoconstriction) is believed to be at least partially responsible for the increased capillary resistance and decreased capillary permeability occuring after hypophysectomy.